Notes on Afrotropical Manota Williston (Diptera: Mycetophilidae), with the description of seven new species - Hippa, Heikki (Zootaxa, 2008)
The following new species are described: Manota clinochaeta (Madagascar), M. cultrigera (Madagascar), M. edentula (Mauritius), M. ephippiata (Uganda), M. macrodon (Madagascar), M. phyllochaeta (Madagascar) and M. uncinata (Madagascar). New records and taxonomic notes are given for M. mabokeensis Matile (Uganda), M. natalensis Jaschhof & Mostovski (South Africa) and M. whiteleyi Jaschhof and Mostovski (Ivory Coast). Taxonomic notes on M. flavipes (Enderlein) (Seychelles) are given and its hypopygium is redescribed.